Chondroitinase ABC in spinal cord injury: advances in delivery strategies and therapeutic synergies - Cunha, Rachel Santana; Rossi, Erik Aranha; Santana, Thaís Alves de; Costa-Ferro, Zaquer Suzana Munhoz; Souza, Bruno Solano de Freitas (Frontiers in Bioengineering and Biotechnology, 2025)
Spinal cord injury (SCI) is a debilitating condition that leads to permanent neurological deficits due to the formation of a glial scar and the accumulation of chondroitin sulfate proteoglycans (CSPGs), which inhibit axonal regeneration. Chondroitinase ABC (ChABC), a bacterial enzyme capable of degrading CSPGs, has emerged as a promising therapeutic strategy for enhancing neural plasticity and functional recovery after SCI. However, clinical translation remains challenging due to the enzyme’s thermal instability, short half-life, and limited penetration into the lesion site. This review provides a comprehensive overview of current strategies for ChABC delivery, including direct infusion, nanoparticles, hydrogels, scaffolds, viral vectors, and stem cell-based approaches. We highlight recent technological advances that improve enzyme stability, targeting, and sustained release, as well as combinatorial therapies that enhance tissue regeneration. Although ChABC monotherapy has shown limited efficacy, its association with other regenerative approaches has demonstrated significant potential in preclinical models. Finally, we discuss the translational challenges and future directions required to bring ChABC-based therapies closer to clinical application in SCI patients.